Cost efficient integration of weather data into agronomic advice - Casteren, Jan Willem van (Technical Centre for Agricultural and Rural Cooperation, 2018)
Two innovative enterprises have integrated a weather service system within an agro advisory service for farmers in East Africa. The eProd handheld device collects the GPS locations and agronomic information such as soil type, seed variety and planting date. aWhere combines this information with their weather data so farmers can now be sent SMS weather forecasts, spray alerts, fertiliser advice and yield projections.